2022
DOI: 10.23887/jpbi.v9i3.43351
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Error in Writing Descriptive Text in The Junior High School Viewed from Its Indicators

Abstract: Students often make mistakes in writing descriptive texts about people, animals, objects, or procedures. When asked about the source of the error, they did not give a clear answer to the question, let alone an explanation of the source of the error. The purpose of this study was to analyze the types of errors made by students and find out why students made mistakes in writing texts. The method used in this study is a qualitative description. Fifteen seventh-grade junior high school students were the subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…Additionally, the finding of this study is also congruent with others studies due to errors in the omission of the language unit (Dewi & Huda, 2020;Kharmilah & Narius, 2019;Setiyorini et al, 2020). It is also in line with previous study which dealing with lexical or diction errors and reinforces (Aziz et al, 2022;Yani, 2022) From the study results, we can understand that most students still made lexical errors. This type of error is crucial to be solved since lexical knowledge is considered a major thing in mastering a foreign language, especially in improving students' comprehension and proficiency (Castellano-Risco et al, 2020;Durbahn et al, 2020;Hsu, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the finding of this study is also congruent with others studies due to errors in the omission of the language unit (Dewi & Huda, 2020;Kharmilah & Narius, 2019;Setiyorini et al, 2020). It is also in line with previous study which dealing with lexical or diction errors and reinforces (Aziz et al, 2022;Yani, 2022) From the study results, we can understand that most students still made lexical errors. This type of error is crucial to be solved since lexical knowledge is considered a major thing in mastering a foreign language, especially in improving students' comprehension and proficiency (Castellano-Risco et al, 2020;Durbahn et al, 2020;Hsu, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These findings regarding carelessness, the finding aligns with previous studies that proved that the students felt they conducted errors, especially in ordering their sentences, because of the transfer of their first language (A. Permatasari, 2020;Yani, 2022). This result is in agreement with other studies, that state the first language (mother tongue) used in communicating in English caused the students to translate their sentences literally and make the sentence construction like in their first language, known as interlingual transfer errors (Islamiyah & Fajri, 2019;Nadya & Muthalib, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Nair and Hui (2018) revealed that the most common errors in descriptive writing were in the areas of sentence structure and grammar. Yani (2021) confirmed that students mostly made errors in grammar. Ismayanti and Kholiq (2020) added that the generic structure was one of the hindrances for students in describing and organizing the ideas properly.…”
Section: Introductionsupporting
confidence: 53%
“…In sum, the simple present is used for events or situations that exist, such as always, usually, or habitually in the past, present, and future. (Yani, 2021), "Descriptive writing is vivid, colorful, and detailed. "…”
Section: Pastmentioning
confidence: 99%
“…As they wrote, they usually focused on writing a suitable title, deciding on the appropriate topic sentence, developing the topic sentence into a whole paragraph, constructing grammatical sentences, arranging supporting sentences coherently, using appropriate words or phrases, and using appropriate writing mechanics Flores in (Yani, 2021) Based on (Hendrickson, 1979), he grouped the errors into two types, they are: 1. Global Errors.…”
Section: This Is a Creative Commons License This Work Is Licensed Und...mentioning
confidence: 99%